Grid: A Python library for molecular integration, interpolation, differentiation, and more - Tehrani, Alireza; Yang, Xiaotian Derrick; Martínez-González, Marco; Pujal, Leila; Hernández-Esparza, Raymundo; Chan, Matthew; Vöhringer-Martinez, Esteban; Verstraelen, Toon; Ayers, Paul W; Heidar-Zadeh, Farnaz (The Journal of chemical physics, 2024)
Grid is a free and open-source Python library for constructing numerical grids to integrate, interpolate, and differentiate functions (e.g., molecular properties), with a strong emphasis on facilitating these operations in computational chemistry and conceptual density functional theory. Although designed, maintained, and released as a stand-alone Python library, Grid was originally developed for molecular integration, interpolation, and solving the Poisson equation in the HORTON and ChemTools packages. Grid is designed to be easy to use, extend, and maintain; this is why we use Python and adopt many principles of modern software development, including comprehensive documentation, extensive testing, continuous integration/delivery protocols, and package management. We leverage popular scientific packages, such as NumPy and SciPy, to ensure high efficiency and optimized performance in grid development. This article is the official release note of the Grid library showcasing its unique functionality and scope.